2019
DOI: 10.1021/acsnano.9b00692
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Diamond–Graphite Bonding: Mechanism of Catalytic Transformation

Abstract: Aberration-corrected transmission electron microscopy of the atomic structure of diamond–graphite interface after Ni-induced catalytic transformation reveals graphitic planes bound covalently to the diamond in the upright orientation. The covalent attachment, together with a significant volume expansion of graphite transformed from diamond, gives rise to uniaxial stress that is released through plastic deformation. We propose a comprehensive model explaining the Ni-mediated transformation of diamond to graphit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 34 publications
8
31
0
Order By: Relevance
“…graphene layers. 18 Similar epitaxial growth of graphene on diamond has been demonstrated by Lee et al 19 and Tulic et al, 20 separately, using conventional CVD. Graphene anchors vertically on the diamond interface (111) plane as well as forming connections with numerous diamond internal (111) planes, based on 1 : 1 and 2 : 1 registries ( Fig.…”
Section: New Conceptssupporting
confidence: 57%
See 1 more Smart Citation
“…graphene layers. 18 Similar epitaxial growth of graphene on diamond has been demonstrated by Lee et al 19 and Tulic et al, 20 separately, using conventional CVD. Graphene anchors vertically on the diamond interface (111) plane as well as forming connections with numerous diamond internal (111) planes, based on 1 : 1 and 2 : 1 registries ( Fig.…”
Section: New Conceptssupporting
confidence: 57%
“…This indicated that the diamond matrix was free from stress which was also supported by the HRTEM images which revealed well-ordered lattices. 19,20 With the structural similarity of diamond (111) and graphene (see Fig. 3a and b) and the role of atomic hydrogen on the kinetics (stability) of diamond in a CVD condition, 4 a formation mechanism of the hybrid structures was proposed to be the inward transformation of diamond (111) planes to graphene layers ( Fig.…”
Section: New Conceptsmentioning
confidence: 99%
“…4 However, when graphene is directly synthesized by Ni-mediated graphitization of NCD, [5][6][7][8][9] actually, the graphitic layers are formed also in the bulk between the NCD nanocrystals. 10 In such case, the quality of SiO 2 interface, as we show here, can play an important role at the electronic transport. In this work, we present transmission electron microscopy (TEM) studies including high-resolution electron microscopy (HRTEM) and electron energy-loss spectroscopy (EELS) maps of cross-sectional NCD samples grown on Si substrates with a 5 nm thick native oxide layer.…”
Section: Introductionmentioning
confidence: 63%
“…These distinguished characteristics are attributed to the lower thicknesses of the NCD ($70 nm) and SiO 2 ($5 nm) layers here, compared to the prior work. 10 The key inuence of these two factors on Ni activity is revealed by the analysis in Fig. 3.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation